Family resilience assessment scale (FRAS): assessing its internal structure in the Brazilian context - Santos de Oliveira, Lays Brunnyeli (2025)
It aimed to gather evidence psychometrics of the Family Resiliency Assessment Scale (FRAS). Two studies were carried out with participants from different states in Brazil. In the first (n = 314), the majority female (56.4%), with an exploratory factor analysis being performed, which suggested a three-factorial structure, with adequate precision. The study 2 (n = 336), the majority female, who undergoing hemodialysis (46.4%). Confirmatory factor analysis corroborated the structure tetra-factorial (family communication and problem solving, maintaining a positive outlook, using social resources and economics, and family spirituality). Therefore, the results showed that the reduced version of FRAS can be an alternative to assess family resilience and its correlates.